Photoreceptor-mediated kin recognition in plants - Crepy, Maria Andrea (2015)
Although cooperative interactions among kin have been established in a variety of biological systems, their occurrence in plants remains controversial. Plants of Arabidopsis thaliana were grown in rows of either a single or multiple accessions. Plants recognized kin neighbours and horizontally reoriented leaf growth, a response not observed when plants were grown with nonkin. Plant kin recognition involved the perception of the vertical red/far-red light and blue light profiles. Disruption of the light profiles, mutations at the PHYTOCHROME B, CRYPTOCHROME 1 or 2, or PHOTOTROPIN 1 or 2 photoreceptor genes or mutations at the TRYPTOPHAN AMINOTRANSFERASE OF ARABIDOPSIS1 gene required for auxin (growth hormone) synthesis impaired the response. The leaf-position response increases plant self-shading, decreases mutual shading between neighbours and increases fitness. Light signals from neighbours are known to shape a more competitive plant body. Here we show that photosensory receptors mediate cooperative rather than competitive interactions among kin neighbours by reducing the competition for local pools of resources.